Clinical and biochemical characteristics for patients with polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes syndrome: a pilot observational study - Pei Li; Ye Zhang; Li-Min Luo; Wen-Qing Wang; Jing Li; Yan Cheng; Xiao Dang; Yang Chen; Wei Jiang (Frontiers in Neurology)
BackgroundPolyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes (POEMS) syndrome is rare life-threatening condition associated with a clonal plasma cell neoplasm.ObjectiveThe aim of this study is to investigate the clinical and biochemical features in patients with POEMS syndrome before and post-therapy.MethodsCharacteristics of demographic information, underlying diseases, clinical manifestations, laboratory indicators, and imaging examination were retrospectively collected when diagnosed and post-therapy in the patients POEMS syndrome between 2018 and 2024.ResultsNineteen newly-diagnosed, treatment-naïve patients with POEMS syndrome were enrolled. The diagnosis of POEMS syndrome was re-analyzed and matched the diagnostic criteria updated in 2023. All patients presented the symptoms of polyneuropathy and positive for M-protein. Most patients suffered with hyperpigmentation (n = 18), organomegaly (n = 18), elevated vascular endothelial growth factor (VEGF) (n = 17), extravascular volume overload (n = 15), sclerotic bone lesions (n = 11), and hypothyroidism (n = 10). Serum alanine aminotransferase, aspartate aminotransferase, total bilirubin, total protein, and albumin levels were down-regulated, while uric acid level was up-regulated in patients with POEMS syndrome. Reduced triiodothyronine, thyroxine, free triiodothyronine levels were negatively correlated with urea nitrogen, creatinine, and uric acid levels in patients with POEMS syndrome. VEGF level, which was negatively correlated with Ca2+ level (r = −0.56), was reduced in most patients with POEMS syndrome receiving bortezomib/ixazomib and lenalidomide/thalidomide therapy. Aspartate aminotransferase, total protein, and estimated glomerular filtration rate levels were increased, while creatinine and uric acid levels were reduced post-therapy in patients with POEMS syndrome.ConclusionPatients with POEMS syndrome had impaired liver and renal function, and effective therapy might partly repair the liver and renal dysfunction.